2011
DOI: 10.1080/14763141.2011.592209
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic drag in cycling: methods of assessment

Abstract: When cycling on level ground at a speed greater than 14 m/s, aerodynamic drag is the most important resistive force. About 90% of the total mechanical power output is necessary to overcome it. Aerodynamic drag is mainly affected by the effective frontal area which is the product of the projected frontal area and the coefficient of drag. The effective frontal area represents the position of the cyclist on the bicycle and the aerodynamics of the cyclist-bicycle system in this position. In order to optimise perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 46 publications
(153 reference statements)
3
105
0
6
Order By: Relevance
“…As aerodynamic drag is dependent on both the drag coefficient and the frontal area, the drag area also dictates the aerodynamic power requirements of riders to maintain a given speed and serves as a performance measure. When force coefficients are reported, the frontal area has been determined using a number of techniques that have been summarised by Debraux et al [28]. These methods usually involve photographs recorded from the frontal views of rider position that are analysed using digital image processing techniques or the weighing of photographs technique [29][30][31].…”
Section: Wind Tunnel Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…As aerodynamic drag is dependent on both the drag coefficient and the frontal area, the drag area also dictates the aerodynamic power requirements of riders to maintain a given speed and serves as a performance measure. When force coefficients are reported, the frontal area has been determined using a number of techniques that have been summarised by Debraux et al [28]. These methods usually involve photographs recorded from the frontal views of rider position that are analysed using digital image processing techniques or the weighing of photographs technique [29][30][31].…”
Section: Wind Tunnel Measurement Techniquesmentioning
confidence: 99%
“…The superscript * symbol refers to when additionalcoefficients have been compared with the experimentally obtained values sources of resistance such as wheel rolling and bearing resistance. Debraux et al [28] reviewed several field testing methods, targeted specifically at separating aerodynamic drag from rolling resistance. Several methods rely on measuring the deceleration of a free-wheeling cyclist at preset intervals and then fitting the data to a simple onedimensional dynamic model of the motion (coast downs).…”
Section: Track and Road Testingmentioning
confidence: 99%
“…We take the system parameters to be values we would typically expect in a race [1,3,16], and assume that the solo rider has the same mass as the mean, M . This gives the dimensionless parameters and scaling factors to be m = 1 , F 0 ≈ 0.028 , L ≈ 510 m, and T ≈ 7.2 s. We also take the initial velocity to be v i = 0.16 (corresponding to about 40km/h or 11m/s, a typical cycling speed).…”
Section: Results and Comparison To Numerical Solutionsmentioning
confidence: 99%
“…The mathematics of drag and air resistance in the context of cycling science is well known and has led to many studies considering strategies for minimizing this drag reduction, ranging from cycling behind a rider (see, for example, [3] for a summary) to the foot positioning on downhill sections [6]. Strategies for short-distance races have been examined (see, for example, [9]) in which minute changes in tactics can be the difference between winning and losing.…”
Section: Introductionmentioning
confidence: 99%
“…The general shape of a rider aboard a bicycle is not streamlined and there are many pockets where air can be trapped and increase drag (Shahbazi, 2007). Meanwhile common aerodynamic drag coefficient values for bicycles can range from 0.6 to 0.8 in racing configurations [5]. Previous research by field testing and wind-tunnel experiments by Garcia-Lopez et al [6] showed that adjustments to the cyclist's position, even minor ones, can result in a decrease of the aerodynamic drag, which indicates the possibility for optimization.…”
Section: Introductionmentioning
confidence: 99%